2017
DOI: 10.4049/jimmunol.1600831
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 4C Protects against Allergic Inflammation: Requirement of Regulatory CD138+ Plasma Cells

Abstract: The regulatory properties of B cells have been studied in autoimmune diseases; however, their role in allergic diseases is poorly understood. We demonstrate that Semaphorin 4C (Sema4C), an axonal guidance molecule, plays a crucial role in B cell regulatory function. Mice deficient in Sema4C exhibited increased airway inflammation after allergen exposure, with massive eosinophilic lung infiltrates and increased Th2 cytokines. This phenotype was reproduced by mixed bone marrow chimeric mice with Sema4C deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…These findings could be explained by elevated levels of IL-4 in Sema3e 2/2 mice upon HDM exposure, which is considered as a key player for Ig class-switching to IgE (35, 36). Xue et al (37) have recently reported that sema4c-deficient mice display an augmented Th2 response, including an increased level of IgE in the serum after allergen challenge. Transfer of sema4cdeficient B cells was shown to induce severe allergic Th2 inflammation in WT mice characterized by high level of IgE in the serum (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings could be explained by elevated levels of IL-4 in Sema3e 2/2 mice upon HDM exposure, which is considered as a key player for Ig class-switching to IgE (35, 36). Xue et al (37) have recently reported that sema4c-deficient mice display an augmented Th2 response, including an increased level of IgE in the serum after allergen challenge. Transfer of sema4cdeficient B cells was shown to induce severe allergic Th2 inflammation in WT mice characterized by high level of IgE in the serum (37).…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al (37) have recently reported that sema4c-deficient mice display an augmented Th2 response, including an increased level of IgE in the serum after allergen challenge. Transfer of sema4cdeficient B cells was shown to induce severe allergic Th2 inflammation in WT mice characterized by high level of IgE in the serum (37). It suggests that semaphorin family members could be essential to regulate B cell response, for example, IgE synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This approach resulted slightly more stringent with regards to the previously published lists of genes significantly regulated by IL-4, since they decreased from 123 genes to 95 genes (87 up and 8 down) in hPBBC and from 189 to 170 genes (130 up and 40 down) in CLL. In addition, recent studies by Xue et al [14] and Mokada-Gopal et al [15] , performed on human tonsil B cells treated for 24 h with anti-CD40 ± IL-4 and mSBC treated for 96 h with LPS + anti-CD40 ± IL-4, respectively, were retrieved from the GEO database (acc. nos.…”
Section: Resultsmentioning
confidence: 99%
“…In the first systematic study which addressed the gene expression response of mouse spleen B cells (mSBC) to IL-4, costimulation with lipopolysaccharide (LPS) and anti-CD40 was used [11] . Then, a few studies have reported the gene expression response of human B cells of diverse origin to IL-4 used as single stimulus [12] , [13] or with anti-CD40 [14] . Recently, a combined transcriptomic and proteomic study performed in mSBC costimulated with LPS and anti-CD40 established that regulation of protein expression by IL-4 occurs mainly at the transcriptional level [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Sections of 0.5mm were stained with H&E and scanned using the digital scanner Aperio AT Turbo. For scoring, peri-bronchial inflammation and the quality of infiltrates were assessed and added using the following grading system: none = 0, mild = 1, moderate = 2, severe = 3 (13).…”
Section: Lung Histologymentioning
confidence: 99%